2004
DOI: 10.1105/tpc.104.025601
|View full text |Cite
|
Sign up to set email alerts
|

The Plant-Specific Kinase CDKF;1 Is Involved in Activating Phosphorylation of Cyclin-Dependent Kinase-Activating Kinases in Arabidopsis

Abstract: Cyclin-dependent kinases (CDKs) play essential roles in coordinate control of cell cycle progression. Activation of CDKs requires interaction with specific cyclin partners and phosphorylation of their T-loops by CDK-activating kinases (CAKs). The Arabidopsis thaliana genome encodes four potential CAKs. CAK2At (CDKD;3) and CAK4At (CDKD;2) are closely related to the vertebrate CAK, CDK7/p40MO15; they interact with cyclin H and phosphorylate CDKs, as well as the C-terminal domain (CTD) of the largest subunit of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 57 publications
(84 reference statements)
3
105
1
1
Order By: Relevance
“…Fig. 3C depicts the phosphopeptide EEYA p SDLEDLK that belongs to the protein "cyclin-dependent kinase F-1 (CDKF-1 or CAK1), which is involved in the control of cell cycle and differentiation during plant development (44) and abiotic or biotic stress (45). The N-glycosylated and Lys-acetylated peptides from DRR206 and CaMCML, respectively, were found up-regulated upon infection while the phosphorylated peptide from CDKF-1was found down-regulated.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 3C depicts the phosphopeptide EEYA p SDLEDLK that belongs to the protein "cyclin-dependent kinase F-1 (CDKF-1 or CAK1), which is involved in the control of cell cycle and differentiation during plant development (44) and abiotic or biotic stress (45). The N-glycosylated and Lys-acetylated peptides from DRR206 and CaMCML, respectively, were found up-regulated upon infection while the phosphorylated peptide from CDKF-1was found down-regulated.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of CDKs requires phosphorylation of a conserved Thr residue in the T-loop by CDK-activating kinases (CAKs) and binding to cyclins (Dewitte and Murray, 2003;De Veylder et al, 2007;Dissmeyer et al, 2007;Harashima et al, 2007;Gutierrez et al, 2009). The Arabidopsis thaliana genome encodes three CAKs (CDKD;1/CAK3, CDKD;2/CAK4, and CDKD;3/CAK2), which are homologous to Kin28 and CDK7 and form different TFIIH-like complexes with cyclin-H;1, TFIIH-2, CAK assembly factor MAT1, and the putative CAK-activating kinase (CAKAK) CDKF;1/CAK1 (Shimotohno et al, 2004(Shimotohno et al, , 2006Van Leene et al, 2010). CDKF;1 appears to be specific to the plant kingdom and phosphorylates the T-loop of CDKD;2 and CDKD;3 in vitro (Shimotohno et al, 2004;Umeda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we identified an alternative MAT1 assembly factor as potential interactor and purified the CDKF1 activating subunit. The interaction with the latter represents a kinase-substrate interaction (Shimotohno et al 2004), which is a typical transient shortliving interaction, explaining why we found it only once in a callus purification experiment. In rice, the direct interaction of CDKD with CDKF1 has been detected earlier using a Y2H assay (Ding et al 2009).…”
Section: Cdkdmentioning
confidence: 74%